Roald Dahl and his chocolate factory - Donkin, Andrew (London Scholastic, 2009)
verybody knows that Roald Dahl wrote brilliant books for children and created a fantastic chocolate factory. But did you know that Roald was a fighter pilot, and a spy in the Second World War? This book contains things you wanted to know about the man with the chocolate factory.
Keywords: fiction